The Value of A 21st Century Education: Nurturing Critical Thinking Skills for a Promising Career and a Happier Life in the 21st Century (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A schooling from the 21st Century is about inspiring students to attain their expertise in this modern environment and encouraging them to gain faith in their skills. With too much knowledge freely accessible to them, talents of the 21st century depend mostly on learning, sharing and smart usage of that information. In our research, we addressed 21st century schooling, emerging media, foreign education as well and concluded that the capacity to think critically and develop, to interact and to connect explicitly sets students on a promising career, but also helps them to lead happy, healthier lives.